Subarachnoid Hemorrhage: Clazosentan vs. Fasudil for Vasospasm Prevention (SAVIOR) Study: Study Protocol for a Prospective, Multicenter, Randomized Trial - Muraoka, Shinsuke; Izumi, Takashi; Takeuchi, Issei; Nishihori, Masahiro; Goto, Shunsaku; Imaoka, Eiki; Kanamori, Fumiaki; Uda, Kenji; Sakamoto, Yusuke; Yokoyama, Kinya; Ando, Masahiko; Kuwatsuka, Yachiyo; et al. (Neurocritical Care, 2026)
Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating condition, with cerebral vasospasm and subsequent delayed cerebral ischemia being key contributors to poor neurological outcomes. In Japan, fasudil is the standard prophylactic agent used to mitigate vasospasm, though its efficacy in improving long-term functional outcomes remains uncertain. Clazosentan, a selective endothelin-A receptor antagonist, has demonstrated potential in reducing vasospasm-related morbidity in phase 3 trials. However, no randomized controlled trial directly comparing the effects of fasudil and clazosentan on functional independence exists in Japan. The primary objective of this study is to determine the superiority of clazosentan over fasudil in enhancing functional outcomes among patients with aSAH. The Subarachnoid Hemorrhage: Clazosentan vs. Fasudil for Vasospasm Prevention (SAVIOR) study is a multicenter, randomized, open-label, parallel-group superiority trial conducted across 21 high-volume stroke centers. Patients with aSAH secured within 48 h of onset will be randomized in a 1:1 ratio to receive either intravenous clazosentan or fasudil. The primary outcome is the proportion of patients achieving a favorable functional outcome (modified Rankin Scale 0-2 at 90 days post-onset). Secondary outcomes include modified Rankin Scale (mRS) score at discharge, incidence of cerebral vasospasm and vasospasm-related delayed cerebral ischemia, and safety profiles, with particular attention to fluid retention-related complications. This trial is the first to directly compare the efficacy and safety of clazosentan vs. fasudil. By selecting the local standard of care as the comparator, the study is designed to generate pragmatic, high-impact evidence that can inform clinical decision-making and potentially reshape treatment guidelines for aSAH management in Japan. It will provide the first high-quality data from a direct comparison of clazosentan and fasudil, in a nimodipine-free population-a clinical question not addressed by previous international trials.